Pengaruh Model Pembelajaran Time TokenTerhadap Motivasi Dan Hasil Belajar Mahasiswa Tentang Biologi Sel Pada Program Studi Pendidikan Biologi Di Universitas Sintuwu Maroso Poso - Shelvy Ferawati Rurua; Andi Tanra Tellu; Samsurizal Suleman (Mitra Sains, 2017)
The objectives of the study is to describe the influence of Time Token learning model towards learning motivation, to describe the influence of Time Token learning model towards students’ learning achievement of Biology Cell, and to determine the relationship between students’ motivation and learning achievement of Biology Cell in Biology Education Studies Program at the Sintuwu Maroso University. The research design uses posttest only control group design in quasi-experiment research. The sample of the research is 79 students. Data were obtained from the learning motivation and learning achievement of biology cell. Data were analyzed using t test and product moment correlation test using SPSS 16.0 for Windows. The results showed that there is significant influence of Time Token learning model toward student’ motivation in learning Biology Cell (t> t table, 1.950> 1.665); there is significant influence of Time Token learning model toward students’ learning achievement of Biology Cell (t> t table, 10.941> 1.665); and there is a positive relationship between learning motivation and learning achievement of Biology Cell in Biology Education Studies Program at Sintuwu Maroso University (r = 0.601 it is the strong category). Based on the results can be concluded that Time Token learning model can improve student’ motivation and learning achievement.